An Experimental Study on the Impact of Resistance and Plyometric Training Programs on Coordinative Abilities and Playing Performance of Cricket Players - Mukhtar Ahmad Wani; Dr. Vikas Saxena (PT. Radja Intercontinental Publishing, 2025)
The current study examines the effects of resistance and plyometric training programs on specific coordinative skills and cricket players' performance using an experimental research design. Modern cricket necessitates elevated levels of coordination, agility, power, and sport-specific skills, rendering scientifically structured training interventions imperative for performance improvement. To assess the efficacy of these training modalities, a sample of cricket players was randomly chosen and allocated into two experimental groups resistance training and plyometric training and a control group adhering to a standard training regimen. The training interventions were conducted over eight weeks, maintaining regulated frequency and intensity. Before and after the training period, standardized and reliable tests were used to measure selected coordinative skills like balance, agility, reaction time, and hand-eye coordination, as well as overall playing performance. Descriptive statistics and analysis of covariance (ANCOVA) were two statistical methods used to look at the data that had been collected. The results showed that both experimental groups had much better coordination skills and playing performance than the control group. Additionally, plyometric training exhibited more pronounced effects on agility and explosive coordination, whereas resistance training had a greater impact on strength-related coordination and performance consistency. The study's results show that structured resistance and plyometric training programs can help cricket players improve their coordination and performance on the field. The study concludes that incorporating these training methods into standard cricket conditioning programs can substantially enhance athletic performance and competitive achievement.